IMPLEMENTASI MEDIA KARTU KOSAKATA DALAM MENINGKATKAN KEMAMPUAN BERBICARA SISWA KELAS V SD NEGERI 096113 TANJUNG SARIBU - JOHAN R MATONDANG; CATHERINE SARAGIH (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The purposes of this study are (1) to find out how to improve speaking skills using vocabulary card media in fourth grade students of SD Negeri 096113 in the 2020/2021 academic year; (2) to determine the form of planning and implementation of learning to speak using vocabulary card media: (3) to find out the obstacles and results obtained from learning to speak using vocabulary card media, consisting of 20 students. This study uses a qualitative approach, because the study seeks to examine more deeply about the improvement of learning outcomes in speaking skills using vocabulary cards in Indonesian learning, which aims to help students express ideas and ideas well. This study also uses 2 (two) cycles starting from February to May 2021. From the results of the learning activities, it can be concluded as follows: (1) learning by using vocabulary card media has a positive impact on improving speaking skills marked by an increase in students' speaking in each cycle, namely the first cycle obtained an average of 66.25 and in the second cycle obtained an average of 80; (2) the application of vocabulary card media in speaking skills has a positive influence, namely students are able to express and express ideas, and the results of students' scores meet the minimum completeness criteria.